2021
DOI: 10.21203/rs.3.rs-851723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Comparison of CSN2 (rs43703011) Beta-Casein Gene Options Frequencies in Different Breeds of Ukraine Cows and the Prospect of Creating Herds with the A2/А2 Genotype

Abstract: Using real-time polymerase chain reaction methods, we have researched the CSN2 polymorphism (GenBank M55158; SNP rs43703011) gene in 4 breeds of cows in the North-East of Ukraine. The observed distributions of genotype frequencies А1/А1, А1/А2, А2/А2 and A1 or A2 alleles varies considerably in different cattle breeds: Lebedyn cattle - 14.6%, 31.7%, 53.7% (0.3 and 0.7); Ukrainian brown dairy breed - 6.8%, 43.2%, 50% (0.28 та 0.72); Simmental cattle - 7.3%, 51.2%, 41.5% (0.33 and 0.67); Ukrainian black speckled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The functions of the genes used in the first approach have been somewhat studied in detail. The surface properties of casein micelles are highly dependent on beta-casein (CSN2), and rs43703011 is associated with A2 milk [33,34]. The statistical analysis showed that polymorphism of the CSN2 gene had a significant effect on the protein content in the milk of the Slovak Holstein cattle.…”
Section: Candidate Genes With Predicted Functionsmentioning
confidence: 99%
“…The functions of the genes used in the first approach have been somewhat studied in detail. The surface properties of casein micelles are highly dependent on beta-casein (CSN2), and rs43703011 is associated with A2 milk [33,34]. The statistical analysis showed that polymorphism of the CSN2 gene had a significant effect on the protein content in the milk of the Slovak Holstein cattle.…”
Section: Candidate Genes With Predicted Functionsmentioning
confidence: 99%